Reform of the London Stock Exchange: the prudential issues - HALL, M.J.B. (PSL Quarterly Review, 2013)
In October 1986 the London Stock Exchange underwent what was termed the Big Bang. This consisted of the removal of fixed commissions on UK securities transactions, the abolition of the single capacity system, and the removal of barriers to entry to UK securities markets. The author considers five prudential issues raised by this event: monopoly power and foreign dominance, international supervisory harmonisation, capital adequacy and managerial competence, the management of 'fall out' (exit from the industry), and conflicts of interest. Three further factors are considered in detail; the regulator's approach to conflicts of interest, the regulation of financial conglomerates, and the implications of the Financial Services Act. JEL: G10, G18